The Application of Pesantren Culture in Forming the Noble Character of Students at Al-Itqon Telogosari Islamic Boarding School in Semarang - Warosah, Romaya Hanik; Savitri, Fania Mutiara (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
The aim of the research was to find out the culture of the Islamic boarding schools at the Al-Itqon Tlogosari Islamic boarding school, Semarang and to find out the application of Islamic boarding schools' culture in forming the akhlakul karimah students at the Al-Itqon Tlogosari Islamic boarding school, Semarang. The method used in this research is a qualitative method, a research procedure that produces descriptive data using a case study approach and using data collection techniques through interviews, observation, and documentation. Using data analysis techniques according to Miles and Hubarman which consist of data reduction, data presentation, and drawing conclusions. Using the data validity test of the source triangulation technique. The results of the study show that the pesantren culture applied in Islamic boarding schools is in the form of the value of simplicity, the value of the relationship between the kiai and students, the value of friendship, and the value of discipline. The application of Islamic boarding school culture at the Al-Itqon Islamic boarding school has become a habit and is applied in the daily activities of the students. The application of Islamic boarding school culture has a positive goal of forming the akhlakul karimah students, this can be seen from the existence of a well implemented Islamic boarding school culture.